SIMULTANEOUS SACCHARIFICATION FERMENTATION MODEL SIMULATION OF BIOETHANOL PRODUCTION FROM BAMBOO SHOOTS: A SYSTEMATIC LITERATURE REVIEW (Jurnal Teknologi Industri Pertanian, 2026)
Bioethanol is an alternative fuel that has the potential to replace fossil fuels because it is renewable and environmentally friendly. One of the potential raw materials for bioethanol production is bamboo shoots, which have lower lignin content than mature bamboo, making them easier to convert into simple sugars. Bioethanol production through Simultaneous Saccharification and Fermentation (SSF) has received significant attention due to its efficiency in enzymatic hydrolysis and fermentation in one step. Bamboo shoots, with lower lignin content compared to mature bamboo, are a promising raw material for bioethanol production. This Systematic Literature Review (SLR) aims to critically analyze previous studies on SSF bioethanol production from bamboo shoots, identify research gaps, and highlight areas that require further investigation. This review focuses on modeling approaches, key process parameters, and microbial interactions in SSF. Unlike previous studies that incorporated Menten kinetics, this review emphasizes Monod kinetics to describe the conversion of substrates into microbial biomass and ethanol. This analysis reveals limitations in current SSF research, including the need for optimal fermentation conditions, microbial strain selection, and better mathematical modeling for process prediction. The findings of this study provide a basis for future research in optimizing SSF for bioethanol production and contribute to the development of more efficient and sustainable bioenergy solutions.Keywords: bioethanol, bamboo shoots, SSF, model simulation, reneawable energy